‘Burning Love’, Living Ngurra: Healing Country, Healing Hearts and Sharing Minds in Dharug Country - Jo Anne Rey; Corina Wayali Norman; Gabrielle Brennan; Emilie Ens; Rosemary Norman-Hill (Journal of Global Indigeneity)
‘Burning Love’ is not just the title of a song sung by Elvis Presley. It is a metaphor for the traditional custodial practice of using cool guwiyang (fire) to care for the environment by Indigenous peoples across the continent called ‘Australia’ for more than 65,000 years. As such it is not only a practice for maintaining Ngurra (Country), but it involves intimate relationality with specific presences, places, and people. As such it involves love: the deep understanding that our wellbeing, today and into the future, relies on Ngurra. Just as in the human realm of love and caring, we understand that our wellbeing relies on the wellbeing of those we love. As such, ‘burning love’ differs vastly from the current fire ‘hazard’ reduction processes that are failing to protect property, human lives, and biodiversity.